ANALISIS FAKTOR PENDORONG DAN PENARIK WISATAWAN UNTUK BERBELANJA DI FACTORY OUTLET KOTA BANDUNG - Irwan Haribudiman (JURNAL NASIONAL PARIWISATA, 2012)
This research was intended to analyze of tourists’ push and pull factors to shop in factory outlet at Bandung. Moreover, the objectives of this research are:(1) to analyze the profile and perception of domestic tourists toward push and pull fac-tors; (2) to know the influences of these drives on the tourists’ visiting frequency; and (3) to count the contribution of each factor toward the frequency of tourists’ visit to the factory outlets each year at Bandung.The research used descriptive analytical method and the data were collected through surveys and questionnaires. The data includes an overview of research area, tourists’ profiles, and tourists’ perceptions about the push and pull factors to shop in factory outlet at Bandung. This research put 97 respondents, and the technique used in this research was accidental sampling.The results of the research could be explained as below. First, the tourists’ profiles based on actual market conditions could be divided into groups as psycho centrist, repeaters, active shoppers, and the price shoppers. Besides, the origin of majority tourists were coming from Jakarta and its surrounding areas who have a fixed job, middle income, and a lifestyle that tends to be wasteful and luxurious. Second, the drive that most influence the tourists to shop is the motive to strengthen family’s bound or friendship. Meanwhile, the variations of good that sold at factory outlets is the main pull factor to travel to these destinations. Third, through the data, it analysis shown that both of two factors were carried out a positive and significant influence toward the frequency of tourists’ visit each year, by giving contribution of 18% for the push factors, and 19% for the pull factor. Furthermore, when both of two factors were combined, it could provide a greater contri-bution value about 26.5%, and the remains of 73.5% is epsilon that were explained by other variables which are not examined in this study.